2023 PNG Rural Household Survey Report - Schmidt, Emily; Fang, Peixun; Kedir Jemal, Mekamu; Mahrt, Kristi; Mukerjee, Rishabh; Rosenbach, Gracie; Yadav, Shweta (International Food Policy Research Institute, 2024)
From May to December 2023, the International Food Policy Research Institute (IFPRI) implemented a rural household survey that collected detailed data on rural household food consumption and expenditures, agricultural production practices, employment profiles, child and mother 24-hour diet recall, and child anthropometry measurements in Papua New Guinea (PNG). The research team carried out the survey, which used location-based sampling, across five agroecological study areas, of which four of the areas were defined using elevation and rainfall variation. The five agroecological survey areas were seasonal highlands, nonseasonal highlands, seasonal lowlands, nonseasonal lowlands, and islands (the islands survey sample was not disaggregated by elevation or precipitation patterns). In identifying seasonal and nonseasonal survey areas, we adapted the rainfall seasonality categories established by Bourke and Harwood (2009), who evaluated the relative difference in rainfall between the wet and the dry season using resource mapping units defined by the PNG Resource Information System (PNGRIS). The areas of the country that experience large seasonal variation in rainfall (heavy to light, depending on the season) are classified as seasonal, whereas the areas that experience moderate to continuously heavy rainfall throughout the year are classified as nonseasonal (see Figure A1.1 in the appendix for the survey seasonality classification by area). In nonseasonal areas, agricultural growing conditions remain similar year-round, whereas seasonal rainfall areas have agricultural conditions that necessitate a variety of production strategies. Lowland and highland areas were defined using elevation data; areas 1,000 meters or more above sea level were classified as highlands, and those below 1,000 meters were classified as lowlands.